Utilização de Geotecnologias: Diagnóstico Ambiental do Estuário do Rio Acaraú, Ceará, Como Estudo de Caso - ARAÚJO, MARIA VALDIRENE; SÁ FREIRE, GEORGE SATANDER (Pesquisas em Geociências, 2007)
<!– .p text-align: justify; –> The Acaraú basin is located to the west of Fortaleza, capital from Ceará state and, it covers an area of 14.500Km² being considered the second largest basin in this state. The study area, which covers 80Km², is in the estuary of the Acaraú river, embracing the munipality of Acaraú and Cruz in the west. The research intended to analyze the geo-environmental conditions, to analyze the use process and occupation and the environmental impacts, as well as to characterize the resident population in the area and to conserve the natural resources in order to guarantee their use by the next generations. The used methodology included pertinent bibliography, pictures and satellite images with good resolution as the images of Quickbird. The geoprocessing activities involved images digital processing of remote sensing and the integration of data in structure of SIG (System of Geographical Information). The obtained results consisted in the integrated environmental analysis generating a proposal of environmental zoning.